THE IMPACT OF TRAINING AND DEVELOPMENT ON EMPLOYEES PERFORMANCE AND PRODUCTIVITY: A CASE STUDY OF OCL INDIA LTD - Rasmita Behera (International Journal of Research Science and Management, 2016)
In this competitive world, training plays an important role in the competent and challenging format of business. Training is the nerve that synthesized the smooth functioning of the organization and enhancing the quality of work life of the employees. Development is a process that leads to qualitative as well as quantitative advancements in the organization, especially at the managerial level, it is less considered with physical skills and is more concerned with knowledge, values, attitudes and behavior in addition to specific skills. The purpose of this paper is to measure the impact of training and development on employee’s performance and productivity. This paper is quantitative in nature. Data for the paper have been collected through primary source that are from questionnaires surveys of Odisha Cement Limited, Odisha. The study result implies that there is a positive impact of training and development in the improvement of productivity and employee’s performance of OCL.